2019
DOI: 10.15406/ghoa.2019.10.00357
|View full text |Cite
|
Sign up to set email alerts
|

First report of Enterobacter soli associated with gastro-hepato infection of farmed fish, Channa striatain Malaysia

Abstract: The freshwater snakehead fish Channa striata is extensively distributed across tropical Africa and Asia. This fish becomes an important commodity in the aquaculture business that has been industrialized very fast over the last ten years. However, diseases brought economic loss to the industry estimated to be in billions. Although wild Channa striata are known to be highly resistant to diseases, the case under captivity may be different. For instance, an occurrence of selective mortality was found in a farm of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
2
0
0
Order By: Relevance
“…The study findings are consistent with other studies conducted in Canada, Greece and Mexico [24][25][26]. Interestingly, the study observed other low plasmid prevalence species that were reported elsewhere in soil samples, fish flesh samples [27][28][29] and pigeon flesh specimens [30] such as Micrococcus sp. Kbs0714, Enterobacter soli and Proteus columbae.…”
Section: Discussionsupporting
confidence: 91%
“…The study findings are consistent with other studies conducted in Canada, Greece and Mexico [24][25][26]. Interestingly, the study observed other low plasmid prevalence species that were reported elsewhere in soil samples, fish flesh samples [27][28][29] and pigeon flesh specimens [30] such as Micrococcus sp. Kbs0714, Enterobacter soli and Proteus columbae.…”
Section: Discussionsupporting
confidence: 91%
“…The study findings are consistent with other studies conducted in Canada, Greece, and Mexico [24][25][26] . Interestingly, the study observed other low plasmid replicon prevalence species that were reported elsewhere in soil samples, fish flesh samples [27][28][29] , and pigeon flesh specimens [30] , such as Micrococcus sp. Kbs0714, Enterobacter soli and Proteus columbae .…”
Section: Discussionsupporting
confidence: 59%
“…The study findings are consistent with other studies conducted in Canada, Greece and Mexico (Boyd et al, 2020;Rodríguez-Medina et al, 2019;Tsakris et al, 2011) where these microbes had low plasmid prevalence. Also, the study revealed low plasmid prevalence species that were reported elsewhere in soil, fish and pigeon samples (Bhassu et al, 2019;Dai et al, 2018;Manter et al, 2011) which are Micrococcus sp. Kbs0714, Enterobacter soli and Proteus columbae.…”
Section: Discussionmentioning
confidence: 53%